If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 11 + 5x Reorder the terms: 5 + 3x = 11 + 5x Solving 5 + 3x = 11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 5 + 3x + -5x = 11 + 5x + -5x Combine like terms: 3x + -5x = -2x 5 + -2x = 11 + 5x + -5x Combine like terms: 5x + -5x = 0 5 + -2x = 11 + 0 5 + -2x = 11 Add '-5' to each side of the equation. 5 + -5 + -2x = 11 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 11 + -5 -2x = 11 + -5 Combine like terms: 11 + -5 = 6 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| -9(v+4)+3v+7=7v+8 | | 3/7=4/x+5 | | -11.2+4(2.1+x)=(0.8) | | 5(t^2-3t+2)=t(5x+2) | | 2x+1/2x+1/2x=360 | | (4x+5)(x-3)=0 | | 1/3y-7/2=-7/4 | | 9/12+2/9 | | 52-5x=2 | | 2x+7=-2x+7 | | 9(b-4)-7b=5(3b-10) | | 1/12y=15 | | 8+4b=18 | | 3/7=-4/x+5 | | (-5/c)=(1/3) | | 1/4(20-4x)=6-x | | 12-q=8 | | x+7/3=7 | | (2/7)=(x/-42) | | -4-x=6x-4 | | y-8+6y=-9+5y+1 | | 12=e/12 | | 7x+8=8+6x | | 4x+11=5x+4 | | x+1.35=2 | | -4/7-1/2v=-2/3 | | 3w=4w+-10 | | (7/10)*(4/5) | | 3-4x=2x+21 | | (x/4)=(3/2) | | 44=28-4(x-2) | | 5/14=p/49 |